English for success in competitive exams - Solomon, Philip Sunil (Oxford University, 2016)
English for Success in Competitive Exams includes both descriptive and objective English for a wide range of competitive examinations for public services. With sections on grammar, vocabulary, reading and writing, this book guarantees improvement in your scores.